Creativity in contemporary higher education in the context of the artificial intelligence expansion - Butrimė, Edita; Zuzevičiūtė, Vaiva (Creativity Studies, 2025)
In the paper it is discussed what are the potential possibilities to foster creativity in contemporary higher education in the context of the artificial intelligence expansion based on theoretical analysis of sources and the findings of a pilot empiric study. The aim of this paper is to discuss aspects for potential development of creativity in higher education in the context of the artificial intelligence expansion. The objectives are organized around the research question: what are the aspects of studies in the context the artificial intelligence expansion that students in higher education experience and note today as relevant for their studies (potentially – for professional activity)? Methods of critical analyses of references, theoretical considerations, reflections on authors’ personal experiences, and a pilot empiric study, involving respondents/students, were employed for the development of the paper. Results of an empiric study are presented together with the conclusions that students in higher education conceptualise expansion of the artificial intelligence quite broadly and to a major degree – optimistically, with some attention on creativity and quite extensive attention to changes in culture.